Design and Fabrication of LC-Oscillator Tool Kits Based Op-Amp for Engineering Education Purpose - Syifaul Fuada; Hakkun Elmunsyah; Suwasono Suwasono (Institute of Advanced Engineering and Science, 2016)
In this paper, a proposed design, fabrication and testing of sine wave oscillator “LC” type (Hartley and Colpitts oscillator) has been performed using five approaches. The first approach proposed design is done theoretically using the basic theorems used to generate oscillations, such as the condition of oscillation criteria and determine the values of capacitor (C) and inductor (L) component, Secondly it is done using simulation technique (LTSpice IV), Thirdly the simulated design is implemented practically using IC OP-AMP 741 with passive elements such as resistors, capacitors and inductors by oscilloscope and frequency generator. Fourthly design the Hartley and colpitts tool kit by 2-D and 3-D, layouting the circuit by Eagle PCB design software then package into tool box which integrated each other. Finaly, the LC-oscillator tool kit was tested such as resistor, capasitor and inductor module and write the result into tables (for jobsheet data).